Hubungan Karakteristik Biometrik Eucalytus pellita Terhadap Kerusakan Karena Angin: The Relationship of The Biometric Characteristics of Eucalytus Pellita Against Wind Damage - Tatik Suhartati; Sugeng Wahyudiono; Ricky Ricky (HUTAN TROPIKA, 2022)
Strong winds that occur can damage the Eucalyptus pellita plant thereby reducing wood production at the end of the rotation. Biometric characteristics are very important to predict the criteria for trees that are at risk of damage due to wind. This study aims to determine the biometric characteristics that play a role in the risk of trees being damaged by wind. The study was conducted on Eucalyptus pellita aged 5 years. The biometric characteristics studied consisted of diameter at breast height (DBH), total height (H) and crown length (CL) as well as the ratio of H/DBH (slenderness inde)x and CL/H (percentage of  crown). Binary logistic regression analysis was used to analyized  the probability of tree damage due to wind. The results showed that the regression model with the independent variable H/DBH was a suitable model. The H/DBH ratio or tree slenderness index is a biometric characteristic that contributes 11,4% to explain the risk of wind damage.   Keywords: binary logistic regression ; percentage of  crown; slenderness index